Conversor CC/CC com dois estágios para aplicação em sistemas fotovoltaicos autônomos de energia - Reis, Francisco Everton Uchôa (2012)
This work presents a study of a DC/DC converter with two stages for implementation of a stand-alone photovoltaic power system. The converter under study consists of two DC/DC converters, in which between them is inserted a battery bank to give continuity to the energy supply in periods when there isn’t solar radiation. All converters used for the composition of the system are of type boost based on the three-state switching cell (TSSC). The first converter has function of to send energy from photovoltaic panels to a battery bank of 48 V formed by four batteries of 12V connected in series, and its function is to allow the photovoltaic panels operation at the maximum power point (MPP). The second stage consists of a converter of high voltage gain, whose role is to raise the 48 V battery bank voltage to 400V DC output bus voltage. To ensure the regulation of voltage at 400 V DC, was implemented the control LQR (Linear Quadratic Regulator). To design the controller LQR, a simplified methodology to obtain a model of the high-gain voltage converter is used. For each stage is presented its theoretical study, analysis and the components were designed and specified. To verify the theoretical analysis, was developed a prototype for each stage and the experimental results are presented in this work.